Why does China prevent North Korea from collapsing? - Ho, Shawn Yuan-Sheng. (2013)
This paper aim to answer a question which remains a puzzle in international relations: Why does China continue to support North Korea and prevent its collapse? Much research has been done China’s pursuit of its various security and economic interests in North Korea. Less research has been conducted on China’s geo-political interests in North Korea (defined here as how China uses North Korea as a tool to enhance its own political position relative to other states in Northeast Asia). Most importantly, there has been no study done on which of these three independent variables – China’s geo-political, economic or security interests in North Korea – is the key variables that makes China do its best to prevent North Korea from collapsing. This paper aims to fill that academic gap. Through a critical analysis of the research done thus far by scholars in this field and through examination of the latest open-source materials, I arrive at the conclusion that China’s North Korea policy is largely driven by a pursuit of its own geo-political interests and less so by its security and economic interests in North Korea.